Healing Sebagai Strategi Coping Stress Melalui Pariwisata - Nurul Hikmah; Nurul Khansa Fauziyah; Minda Septiani; Desy Murni Lasari (Indonesian Journal of Tourism and Leisure, 2022)
“Healing" has become a popular trend in Indonesia. Although it differs from the actual meaning of "healing" in a psychological perspective, "healing" describes recovery and healing in general, including the activities one does during the holidays to recover from the physical and mental boredom and fatigue one is experiencing. The literature on "healing" as a stress coping strategy in the tourism frame has not been discussed in detail in previous studies. This article aims to discuss the trend of "healing" as a stress coping strategy in the tourism context that can be practiced in tourism development in Indonesia. Coping stress is an individual response as an effort that can be made to obtain peace and inner peace against the type of stress experienced. This study uses a systematic literature review approach. There are two important findings in this study, first, coping with stress through the trend of "healing" is included in the type of emotion focused coping, which is a conscious adjustment. Second, "healing" activities which are carried out in the form of fun and calming activities such as nature tourism, culinary tourism, cultural tourism and special interest tourism. Optimizing stress coping strategies through tourism is an important step that can be taken to support the achievement of individual well-being which can develop interest in tourism visits in Indonesia